Analysis of tensile properties in tempered martensite steels with different cementite particle size distributions - Kengo Sawai; Keiya Sugiura; Toshio Ogawa; Ta-Te Chen; Fei Sun; Yoshitaka Adachi (AIMS Materials Science)
In this study, the tensile properties of tempered martensite steel were analyzed using a combination of an experimental approach and deep learning. The martensite steels were tempered in two stages, and fine and coarse cementite particles were mixed through two-stage tempering. The samples were heated to 923 and 973 K and held isothermally for 30, 45, and 60 min. They were then cooled to 723, 773, and 823 K; held isothermally for 30, 45, and 60 min; and furnace-cooled to room temperature (296 ± 2 K). The combination of low tempering temperature and short holding time in the first stage resulted in high tensile strength. When the tempering temperature at the first stage was 923 K, the combination of low tempering temperature and long holding time at the second stage resulted in high total elongation. This means that decreasing the number of coarse cementite particles and increasing the number of fine cementite particles improve the strength–ductility balance. Using the results obtained by the experimental approach, an image-based regression model was constructed that can accurately suggest the relationship between the microstructure and tensile properties of tempered martensite steel. We succeeded in developing image-based regression models with high accuracy using a convolutional neural network (CNN). Moreover, gradient-weighted class activation mapping (Grad-CAM) suggested that fine cementite particles and coarse and spheroidal cementite particles are the dominant factors for tensile strength and total elongation, respectively.